The Revitalization Of Character Education Based On Pancasila In The Global Era - Margison A. W. B. Blegur (Universitas Sebelas Maret, 2021)
There is character degradation caused by rapid global progress and development and indirectly demands that humans be able to adapt to existing needs, while the purpose of writing this scientific paper is how the Indonesian people are more aware of and appreciate the importance of living up to existing values. the values contained in Pancasila. In writing this scientific paper the writer uses historical research methods. In this historical research method, the researcher uses several reference sources in the form of relevant journals and books that support this writing. The result is that there are several obstacles that often occur on the surface of everyday life, namely: first, a lack of mutual respect among others; second, the things of the World take top priority in terms of living together (the attitude of Individualism); third, decreased practice of the values that exist in Pancasila. An attitude of mutual respect and prioritizing togetherness is very important to be instilled back in the community so that these values are still upheld because they are part of the values of Pancasila and the NKRI slogan, namely Bhineka Tunggal Ika.